Relationship between Internal Locus of Control and Employees' Ethical Behaviour in Organisations - Halizah, Siti Nur; Mardikaningsih, Rahayu (Metromedia, 2022)
In social life, ethical behavior is very important. This is because, the interaction between individuals in society is strongly influenced by ethical values. Basically, it can be said that the awareness of all members of society to behave ethically can build a bond and social harmony. However, we cannot expect everyone to behave ethically. Ethical behavior can be formed from good self-control, especially control from within the individual himself or is called an internal locus of control so that unethical individual behavior can be controlled. The purpose of this study is to determine the relationship between internal locus of control and ethical behavior of employees in organizations. With the role of this internal locus of control, it is expected that the ethical behavior of employees within the organization can be well formed.